2022
DOI: 10.1177/02676591221105603
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outcomes of venovenous extracorporeal membrane oxygenation for acute respiratory failure vs historical cohort of non-COVID-19 viral infections

Abstract: Introduction Veno-venous extracorporeal membrane oxygenation (VV ECMO) has become a support modality for patients with acute respiratory failure refractory to standard therapies. VV ECMO has been increasingly used during the current COVID-19 pandemic for patients with refractory respiratory failure. The object of this study was to evaluate the outcomes of VV ECMO in patients with COVID-19 compared to patients with non-COVID-19 viral infections. Methods We retrospectively reviewed all patients supported with VV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
7
4
0
Order By: Relevance
“…Nonetheless, patients with COVID-19 spent significantly longer periods of time on MV before ECMO cannulation (6.5 (2.0–11.0) days) with lower but still high respiratory pressures. Dave et al also reported the difference in the length of MV in patients with COVID-19 vs patients with other viral pneumonia before ECMO, which were shorter as in our study (1.0 (0.25–3.0) vs 3.0 (1.5–4.5) days) [ 20 ]. Barbaro et al reported MV before ECMO in COVID-19 patients in 4.3 (2.0–6.5) days, whereas in the study by Widmeier et al in Germany, it was 7.8 (4–12.7) days.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Nonetheless, patients with COVID-19 spent significantly longer periods of time on MV before ECMO cannulation (6.5 (2.0–11.0) days) with lower but still high respiratory pressures. Dave et al also reported the difference in the length of MV in patients with COVID-19 vs patients with other viral pneumonia before ECMO, which were shorter as in our study (1.0 (0.25–3.0) vs 3.0 (1.5–4.5) days) [ 20 ]. Barbaro et al reported MV before ECMO in COVID-19 patients in 4.3 (2.0–6.5) days, whereas in the study by Widmeier et al in Germany, it was 7.8 (4–12.7) days.…”
Section: Discussionsupporting
confidence: 61%
“…In studies from Germany and France, the overall 90-day mortality was 52–68%, again depending on the wave of the pandemic [ 22 , 23 ]. Barbaro and Dave demonstrated better survival in patients with COVID-19 compared with reports from France and Germany (including our results), apparently due to better patient selection; the average age in the first reports was 47–50 years compared to 59–61 in other reports [ [20] , [21] , [22] , [23] ]. In addition, the group studied by Dave et al did not include patients with ischemic heart disease; Barbaro et al reported that only 3–5% of patients had a pre-existing heart disease in the COVID-19 group [ 20 , 21 ], whereas 21.1% of patients with COVID-19 in our study had pre-existing ischemic heart disease.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Some studies compared ECMO in non-COVID-ARDS patients and COVID-ARDS patients. Although similar results were gathered about oxygenation (99,100), the treatment time and complications were different. Chandel et al (99) analyzed 9,271 patients who required ECMO between 2017 and 2021.…”
Section: Ecmo In Non Covid-ards Versus Covid-ards Patientsmentioning
confidence: 62%